FROM CLOVIS TO CHARLEMAGNE - Collins, Roger, 1949- Link ([S.l.])
1 online resource
Keywords: This book is a collection of papers on Frankish historiography in the Merovingian and early Carolingian periods, from the late sixth to early ninth centuries, and studies numerous individual texts, evaluating their witness to the events they describe. It also includes hitherto unpublished items on the so-called Chronicle of Fredegar, in both its original and eighth-century versions, and also an entirely new article on the Merovingian dynastic crisis of 613, along with a general introduction and a bibliography of its author's writing.Particular attention is focused on the element of deception, deliberate or otherwise, in the narrative accounts of some of the Frankish histories and chronicles and on the way they were written in order to promote specific interpretations of certain individuals and events, or in some cases to conceal their very existence. Certain central episodes such as the imperial coronation of Charlemagne are examined to detect the ways in which they were interpreted and presented in contemporary texts.From Clovis to Charlemagne: Frankish History and Historians will appeal to academics and students interested in the history of early medieval France, the processes of historical composition in that period, the study of manuscripts relating to it and the wider questions about historical understanding and the interpretation of evidence.